2023
DOI: 10.1002/apxr.202200119
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐Dimensional Topological Fermions in Electrides

Abstract: Topological electrides have attracted extensive attention in various fields, for example, electrocatalysis, spintronics, electron emitters, etc., due to their non-trivial topological surface states and unique electronic properties. It is well known that topologically protected nontrivial surface states are not broken by external perturbations and further exhibit high carrier mobility and high electron density on some specific surfaces. In addition, electrides usually possess a lower work function due to the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 131 publications
0
3
0
Order By: Relevance
“…87–91 These potential applications of topological materials are precisely due to the presence of “robust surface band structures”. Currently, based on the dimensions of degenerate bands, TSMs can be classified into nodal point semimetals (two (Weyl) -/triple-/four (Dirac) -/six-/eight-fold degenerate points), nodal line semimetals, and nodal surface semimetals, 92–99 as shown in Fig. 5a.…”
Section: Properties Of Electridesmentioning
confidence: 99%
See 1 more Smart Citation
“…87–91 These potential applications of topological materials are precisely due to the presence of “robust surface band structures”. Currently, based on the dimensions of degenerate bands, TSMs can be classified into nodal point semimetals (two (Weyl) -/triple-/four (Dirac) -/six-/eight-fold degenerate points), nodal line semimetals, and nodal surface semimetals, 92–99 as shown in Fig. 5a.…”
Section: Properties Of Electridesmentioning
confidence: 99%
“…Since then, researchers have discovered multiple types of topological electrides, including Dirac electride Ca 3 Pb, 7 ferromagnetic nodal line electride Gd 2 C, 8 0D electrides Li 12 Mg 3 Si 4 /C12A7:e − with a six-fold degenerate point, 46,98 Ba 4 Al 5 with multiple topological states (namely Weyl points, nodal lines, and nodal surfaces), 62 nodal surface electrides Ba/Sr 3 MnN 3 , 65 Dirac nodal line electride Ba 3 N, 66 etc. In 2023, our team 99 carried out a comprehensive review of the development and current status of topological electrides, as shown in Fig. 6a.…”
Section: Properties Of Electridesmentioning
confidence: 99%
“…Two-dimensional (2D) multiferroics and quantum topological phases are two fascinating research topics in condensed matter physics 1–6 that have been attracting significant research interest. Symmetry plays a crucial role in investigating these two fields.…”
Section: Introductionmentioning
confidence: 99%